Immunization Status Related to Acute Respiratory Infections in Toddlers in Takallar District, Indonesia - Ibrahim, Irviani Anwar; Nadimin, Nadimin; Salsabilah, Musfirah (Al-Sihah: The Public Health Science Journal, 2021)
Acute Respiratory Infection (ARI) is the main cause of mortality and morbidity in children, especially in children under five, so it is necessary to know the risk factors for children's health. This study aimed to determine the relationship between exclusive breastfeeding, immunization status, and mother's knowledge with the incidence of ARI in children aged 12-59 months. This research was a cross-sectional study located in Takalar Regency which is devoted to Pattallassang Village. This study focused on 82 toddlers/respondents in the research location. The sampling technique used was accidental sampling. A structured questionnaire was used to collect data. The frequency and proportion were calculated as the descriptive part of the analysis while the Qui/Fisher Exact test was performed as an inferential analysis using SPSS. This study showed that there was no significant relationship between exclusive breastfeeding and the incidence of ARI under five with a value of p = 0.341, there was a relationship between immunization status and the incidence of ARI in infants with a value of p = 0.045, and there was no relationship between maternal knowledge and the incidence of ARI under five with p-value = 0.072. This study found that ARI was common in children under five in the study area. The results of the study indicate the need to increase maternal knowledge about risk factors for ARI, its signs, and symptoms, prevention, and treatment.